Kontribusi Pajak Hiburan terhadap Pendapatan Asli Daerah (PAD) Kota Surabaya Tahun 2021-2023 - Joceline Larissa Pratama Ginting; Nadia Ayu Ardiani; Cahya Amalia Zahra; Siti Nur Fahreza Irena; Ahmad Fikri Naufal Akbar; Amanda Adzkiyah; Revienda Anita Fitrie; Melda Fadiyah Hidayat (CV. ALIM'SPUBLISHING, 2026)
This research is driven by Law Number 1 of 2023 concerning Financial Relations between the Central Government and Regional Governments (HKPD), which reclassifies several taxes, including entertainment tax, into the Category of Goods and Services Tax (PBJT). This policy is further regulated by Surabaya City Regional Regulation Number 7 of 2023. This study aims to analyze the contribution of entertainment tax within the PBJT framework toward Surabaya's Local Generated Revenue (PAD) from 2021 to 2023. Using a descriptive quantitative approach, data were collected from the Surabaya City Budget Realization Report (LRA) and other official documents, then processed using RStudio. The results indicate that while entertainment tax realization increases annually, its contribution to Surabaya's PAD remains significantly low, averaging below 2%. This suggests that entertainment tax is not yet a primary source of revenue for the city. Based on these findings, the Surabaya City Government is expected to tighten supervision over entertainment transactions through digital systems to minimize fraud risks and conduct comprehensive data updates on new entertainment venues to maximize tax collection.